White Matter Alteration of the Cingulum in Parkinson Disease with and without Dementia: Evaluation by Diffusion Tensor Tract–Specific Analysis - Kamagata, K.; Motoi, Y.; Abe, O.; Shimoji, K.; Hori, M.; Nakanishi, A.; Sano, T.; Kuwatsuru, R.; Aoki, S.; Hattori, N. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: In PD, the neurodegenerative process begins in the brain stem and extends to the limbic system and finally into the cerebral cortex. We used diffusion tensor tractography to investigate the FA of the cingulate fiber tracts in patients with PD with and without dementia. MATERIALS AND METHODS: Fifteen patients with PD, 15 patients with PDD, and 15 age-matched healthy controls underwent diffusion tensor imaging with a 3T MR imager. Diffusion tensor tractography images of the anterior and posterior cingulate fiber tracts were generated. Mean diffusivity and FA were measured along the tractography of the anterior and posterior cingulate fiber tracts. One-way ANOVA with the Scheffé post hoc test was used to compare results among the groups. RESULTS: FA was significantly lower in patients with PDD than in healthy controls in both the anterior and the posterior cingulate fiber tracts (P = .003, P = .015) and significantly lower in patients with PD than in healthy controls (P = .003) in the anterior cingulate fiber tract. There were no significant mean diffusivity differences among the groups. MMSE and FA values of the anterior cingulate fiber tracts in patients with PDD were significantly correlated (r = 0.633, P < .05). CONCLUSIONS: The reduced FA in patients with PD and PDD might reflect neuropathologic changes such as Lewy body pathology in the cingulate fibers. This abnormality might contribute to the dementing process in PD. CFTcingulate fiber tractFAfractional anisotropyHSDHonestly Significant DifferenceMDmean diffusivityMMSEMini-Mental State ExaminationPDParkinson diseasePDDParkinson disease with dementiaUPDRSUnified Parkinson's Disease Rating Scale